2021
DOI: 10.1055/s-0041-1730993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Septoplasty with Nonsurgical Management in Improving Nasal Obstruction in Patients with Deviated Nasal Septum – A Randomized Clinical Trial

Abstract: Introduction In the current era, the major indication for septoplasty is nasal obstruction due to deviated nasal septum (DNS). Even though septoplasty is a commonly performed surgery, its effectiveness in relieving nasal obstruction in DNS has not been proven. Objective The present study involved the measurement of both objective (nasal patency) and subjective (quality of life measures) outcome measures for the evaluation of the efficacy of septoplasty as compared with medical management. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A notable disparity in symptom scores and PNIF values was observed when comparing the improvement in scores between the two groups from baseline to 3 and 6 months. Septoplasty demonstrated superior effectiveness in mitigating nasal obstruction compared to nonsurgical management [15].…”
Section: Discussionmentioning
confidence: 96%
“…A notable disparity in symptom scores and PNIF values was observed when comparing the improvement in scores between the two groups from baseline to 3 and 6 months. Septoplasty demonstrated superior effectiveness in mitigating nasal obstruction compared to nonsurgical management [15].…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have shown that septoplasty with or without turbinoplasty is effective in improving symptoms of nasal obstruction, especially when compared to nonsurgical medical treatment. [8][9][10][11] However, most of these studies and nearly all current reviews focus primarily on short-term (<12 months) outcomes. Whether or not these high septoplasty success rates persist years after surgery remains unanswered, as some long-term studies suggest that patient symptoms may worsen again over time.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that septoplasty with or without turbinoplasty is effective in improving symptoms of nasal obstruction, especially when compared to nonsurgical medical treatment 8–11 . However, most of these studies and nearly all current reviews focus primarily on short‐term (<12 months) outcomes.…”
Section: Introductionmentioning
confidence: 99%